Количественная оценка адаптации занятости населения в российских регионах к условиям неопределенности - Fedchenko, Anna A; Dorokhova, Natalya V; Dashkova, Ekaterina S (Ekonomika regiona, 2023)
Volatility, uncertainty, complexity and ambiguity (VUCA), characteristic for current socio-economic development, significantly affect the vital activity of society, as well as the fundamental principles of economic development. This situation requires the creation and implementation of adaptation mechanisms. The study aims to quantify the adaptation of employment to the conditions of the VUCA world in Russian regions. It is hypothesised that the employment of the population in Russian regions with different levels and types of economic development is not adapted to the conditions of the VUCA world. The article analysed a theoretical and methodological platform for examining the labour market and employment that presents Russian and foreign experience. The study revealed the effects of the VUCA world on employment: accelerated response of quantitative employment parameters to economic changes (including by increasing the mobility of workers); post-industrial transformation of the employment structure; formation and dissemination of non-standard forms of employment. The developed methodology for assessing the adaptation of employment to the conditions of the VUCA world was applied to evaluate the key characteristics of this process. The methodology was tested in a number of Russian regions that differ in the level and type of economic development by analysing statistical data for the period 2014–2019. At the present stage, a low and average degree of adaptation of employment is recorded, regardless of the socio-economic development of regions. The proposed comprehensive recommendations are aimed at solving the key problems of adapting employment to the conditions of the VUCA world and are addressed to the subjects of social and labour relations.